Pengaruh Disiplin Kerja, Pengalaman Kerja, dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT Al-Shofa Duta Mandiri - Latifa, Najwa; Agusdin, Agusdin; Suryatni, Mukmin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to determine the Influence of Work Discipline (X1), Work Experience (X2), and Organizational Commitment (X3) on Employee Performance at PT Al-Shofa Duta Mandiri Mataram. The type of research used is causal associative research. The technical analysis used is Multiple Linear Regression using SPSS. In this study, a sample determination technique was used by the saturated sampling method or census, so that the respondents in this study were all employees of PT-Al-Shofa Duta Mandiri Mataram totaling 50 employees. The results of the analysis showed that: (1) Work Discipline had a positive and significant effect on Employee Performance at PT-Al-Shofa Duta Mandiri Mataram (2) Work Experience had a positive and significant effect on Employee Performance at PT-Al-Shofa Duta Mandiri Mataram (3) Organizational Commitment had a positive and significant effect on Employee Performance at PT-Al-Shofa Duta Mandiri Mataram. With the presentation of the results of the analysis above, the company can pay more attention to the environment around the workplace, the company must be able to overcome the problems around the workplace so that employees are comfortable working, then can increase work activities in the team as well as an assessment of employee attitudes and free employees to innovate so that employees feel recognized and still maintain a state where employees can enjoy all existing infrastructure,  With the help of infrastructure, employees will find it easier to complete tasks, all of which are done to improve employee performance.